Intraocular pressure fluctuation in healthy and glaucomatous eyes: a comparative analysis between diurnal curves in supine and sitting positions and the water drinking test - Caiado, Rafael Ramos [UNIFESP] (2014)
Purpose: To compare intraocular pressure (IOP) using the simplified daily tensional curve (SDTC) between supine and sitting positions in terms of peak levels and amount of fluctuation in both, glaucomatous and healthy subjects. The secondary endpoint was the comparison of these measures with those derived from the water drinking test (WDT). Methods: Thirty patients with primary open-angle glaucoma (POAG) that were undergoing medical therapy and 30 healthy subjects were enrolled in this study. Each patient underwent a diurnal curve between 8 am and 4 pm. After lying down for 5 minutes, the IOP was measured with the Perkins tonometer. Patients were instructed to sit in the upright position for 5 minutes and the tonometry was repeated. At 4:15 pm, the WDT test was performed. Fluctuation was defined as the difference between the highest and the lowest IOP readings (range). The Student's t test was used to assess differences and a P value <0.05 was considered to be statistically significant. Results: The diurnal curve in the supine position demonstrated higher IOP average values (on average 3-4 mmHg higher) compared to the sitting position (p<0.0001) for both groups. IOP peaks were higher in the supine position; however, the IOP range was essentially the same between the three methods. Treated glaucomatous patients had higher IOP levels in all measurements, but the fluctuation for all tests performed appeared to be similar to that of healthy patients. Conclusion: The data suggested that WDT can be used to estimate the diurnal IOP peak and fluctuation observed in the SDTC of the supine position for treated glaucomatous patients. Further studies can compare the possible correlation between the WDT results and those obtained from nocturnal supine measurements.